An IFFT/FFT size efficient improved ACO-OFDM scheme for next-generation passive optical network - SANYA, MAX FREJUS O.; AUPETIT-BERTHELEMOT, Christelle (My University, 2016)
In this paper, we propose for the first time, to the best of our knowledge, a novel Improved Asymmetrically Clipped Optical OFDM scheme namely, Eff-IACO-OFDM. This technique employs a novel approach to get real OFDM signals suitable for PON IM/DD systems with no use of Hermitian symmetry. It has relative low computational complexity. The system was analyzed over both an AWGN channel and realistic PON fiber link. Over an AWGN channel, it achieves up to 3 dB gain in optical power in comparison with conventional ACO- OFDM and similar performance as Noise Cancellation ACO- OFDM (NC-ACO) and Diversity-Combined ACO-OFDM (DC- ACO). It offers improvement of 20 km distance transmission with computational complexity savings of 8% compared to ACO- OFDM and similar performance as DC-ACO with very low complexity. We showed by numerical simulation that 11.3 Gb/s transmission with 32 users is possible through 50 km SSMF link by using the proposed Eff-IACO-OFDM technique. As a result, it seems to be an interesting candidate and novel modulation scheme for NG-PON cost-sensitive applications.
Keywords: Passive Optical Networks; IM/DD systems; ACO-; OFDM; Computational complexity